PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 29 GAJAH SAKTI - Sukria, Sukria; Antosa, Zariul; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted because of low learning outcomes IPA fourth grade students of SDN 29 Mandau sub Gajah Sakti. Of the 25 students who achieve KMM total of 15 students with classical completeness (60%), while the students who did not complete 10 people with a percentage (40%). The purpose of this research is to improve student learning outcomes IPA fourth grade SDN 29 Gajah Sakti with the implementation of Problem Based Learning Model (PBM). The results obtained by the average value is 65 increased in the first cycle as much (20.86%) with an average of 81 and the second cycle increased again as many times (30, 29%) with the average score becomes 82.4. At the base score only mastery learning outcomes IPA (43.75%) did not complete. Once applied the model teacher Problem Based Learning (PBM) in the first cycle is complete classical completeness increased to 85%, in the second cycle was obtained classical completeness 85% complete. Teacher activity in the first meeting of the first cycle of 85% in both categories. The second meeting in the first cycle increased to 90% in the excellent category. In the second cycle, the first meeting of the activities of teachers increased by 95% in the excellent category. at a second meeting 90% with very good category. Student activities in the first cycle of the first meeting of student activity gets a percentage of 80% in both categories. at the second meeting of the first cycle to 85% in the second cycle either category. At the first meeting of the second cycle of 90% for category very well. At the second meeting of the second cycle remains 90% with very good category.Key Words: Problem Based Learning, Learning Outcomes IPA